1986
DOI: 10.1007/bf01983819
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies on larval growth ofPolydora ligni, Polydora ciliata, andPygospio elegans (Polychaeta, Spionidae)

Abstract: The spionid polychaete species Polydora ligni, P. cfliata, and Pygospio elegans were cultivated in the laboratory over several successive generations. A flow-through cultivation system for Polydora spp. is described. Duration of life cycles (time from hatching of the larva to first reproduction) and life spans (hatching to death) of these species were not significantly influenced by the degree of inbreeding nor by individual age of the parents. Minimum time from metamorphosis (15-setiger stage) to first hatchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Larvae metamorphosed at 18 d, reached sexual maturity at 37 d, and formed egg capsules by ca 53 d ( h c e 1975). These results agree with studies by Anger et al (1986) who found that at 12 and 18°C Polydora development from hatching to metamorphosis took 16 to 28 d and 9 to 11 d, respectively, while first reproduction occurred about 33 d after settlement at 18OC. Anger et al (1986) found that the average life span of P. ligniin the laboratory was 13 mo.…”
Section: General Ecology and Life Cyclesupporting
confidence: 92%
“…Larvae metamorphosed at 18 d, reached sexual maturity at 37 d, and formed egg capsules by ca 53 d ( h c e 1975). These results agree with studies by Anger et al (1986) who found that at 12 and 18°C Polydora development from hatching to metamorphosis took 16 to 28 d and 9 to 11 d, respectively, while first reproduction occurred about 33 d after settlement at 18OC. Anger et al (1986) found that the average life span of P. ligniin the laboratory was 13 mo.…”
Section: General Ecology and Life Cyclesupporting
confidence: 92%
“…Anger et al (1986) fed 11 species of phytoplankton (including diatom, dinoflagellates, Haptophyceae and Chlorophyceae) to the three spionid polychaete species, and revealed that T. rotula led to a relatively high growth rate of spionid larvae. Diatoms are a major component of spring phytoplankton blooms and it is reported that T. nordenskioeldii and Chaetoceros debilis are major components of spring phytoplankton blooms in Onagawa Bay (Inoue 1995;Sato 1996;Nakamura 2007).…”
Section: Seasonal Change Of Planktonic Polychaete Larvaementioning
confidence: 99%
“…Rogers et al 1995). Anger et al (1986) determined the mean planktonic period of larval developnlent in Pygospio elegans larvae, hatched at 3 setigers in the laboratory, at 20 to 30 d at 1B0C, and 60 to 70 d at 6OC. There is therefore potential for planktonic larval mediated dispersal in this species.…”
Section: Genetic Variabilitymentioning
confidence: 99%